Pengaruh Kuat Arus Listrik Dan Waktu Proses Anodizing Dekoratif Pada Aluminium Terhadap Kecerahan Dan Ketebalan Lapisan - Nitya Santhiarsa, I Gst. Ngr. (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010, 2012)
To increase assess aluminium of decorative aspect hence finishing processes must be used, like coloringprocess. Hence layer anodizing developed now where you can make aluminum metal look more interesting so thefinish can increase the economic value. Anodizing is the process formation of oxide layer on the metal with themetal, especially aluminum reacting with oxygen (O2) from the electrolyte sulphate acid (H2SO4).This research uses2024-T3 aluminum metal as a parent to be coated, with the electric current treatment 1 Ampere, 2 Ampere, Ampere,and 3, and changes in immersion variations time 10 minutes, 20 minutes, and 30 minutes. Tests performed includetesting the brightness (light illumination) and layer thickness measurement.The result of research show that bestvalue for the examination of brightness obtained at electrics current 1 ampere and time anodizing 10 minute equal to11519.53 lumens/m2 and thickness obtained at electrics current 3 ampere and anodizing time 30 minute equal to 5?m, value lowest for the examination of brightness obtained at electrics current 1 ampere and time anodizing 10minute equal to 10180.05 lumens/m2 and thickness obtained at electrics current 3 ampere and anodizing time 30minute equal to 2?m
Keywords: Aluminum Anodizing, Current, Anodizing Time, Brightness, Thickness Coatings